2020
DOI: 10.1051/0004-6361/202038378
|View full text |Cite
|
Sign up to set email alerts
|

Extreme intra-hour variability of the radio source J1402+5347 discovered with Apertif

Abstract: The propagation of radio waves from distant compact radio sources through turbulent interstellar plasma in our Galaxy causes these sources to twinkle, a phenomenon called interstellar scintillation. Such scintillations are a unique probe of the micro-arcsecond structure of radio sources as well as of the sub-AU-scale structure of the Galactic interstellar medium. Weak scintillations (i.e. an intensity modulation of a few percent) on timescales of a few days or longer are commonly seen at centimetre wavelengths… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…Apart from the science planned for Apertif, its large FoV implies that the potential for detecting rare objects or making serendipitous discoveries is high. This is illustrated by the fact that in the survey data taken so far, 16 intra-hour variable radio sources were found serendipitously (Oosterloo et al 2020). Such variable sources are among the rarest objects on the sky.…”
Section: Serendipitous Discoverymentioning
confidence: 96%
“…Apart from the science planned for Apertif, its large FoV implies that the potential for detecting rare objects or making serendipitous discoveries is high. This is illustrated by the fact that in the survey data taken so far, 16 intra-hour variable radio sources were found serendipitously (Oosterloo et al 2020). Such variable sources are among the rarest objects on the sky.…”
Section: Serendipitous Discoverymentioning
confidence: 96%
“…Apart from the science planned for Apertif, its large field of view implies that the potential for detecting rare objects or making serendipitous discoveries is high. This is illustrated by the fact that in the survey data taken so far, 16 intra-hour variable radio sources were found serendipitously (Oosterloo et al 2020). Such variable sources are among the rarest objects on the sky.…”
Section: Serendipitous Discoverymentioning
confidence: 96%
“…As the velocity of the Earth changes through the year, the rate of scintillation changes. This annual modulation, or annual cycle, of the scintillation rate was instrumental in establishing the scintillation nature of the IHV phenomenon (Jauncey et al 2000;Rickett et al 2001) and can be used to determine the velocity of the screen along with the characteristic scale, degree of anisotropy and orientation of the scintillation pattern (e.g., Jauncey & Macquart 2001;Dennett-Thorpe & de Bruyn 2003;Oosterloo et al 2020).…”
Section: Kinematic Analysismentioning
confidence: 99%
“…The method, described in detail in Bignall et al (2019), is designed to allow quantitative inference on the scintillation rate for epochs near standstills (when the Earth velocity is close to that of the screen) where traditional ACF HWHM estimates struggle due to very slow variations. It has been shown to produce results that closely follow the traditional ACF analysis on fast epochs, where comparison is possible (Oosterloo et al 2020). Unlike Bignall et al (2019), we used single light curves (per epoch, per source) due to observed relatively broadband nature of the scintillation relative to the ASKAP bandwidth.…”
Section: Kinematic Analysismentioning
confidence: 99%
See 1 more Smart Citation